2013
DOI: 10.2298/ciceq120531095b
|View full text |Cite
|
Sign up to set email alerts
|

Chromium (VI) removal from aqueous solutions by purolite base anion-exchange resins with gel structure

Abstract: The removal of Cr (VI) from aqueous solution using two strong base anionic resins with gel structure, purolite A-400 (styrene-divinylbenzene matrix) and purolite A-850 (acrylic matrix) was investigated using a batch technique. The sorption efficiency was determined as a function of phases contact time, solution pH, resin dose, temperature and initial Cr (VI) concentration. The percentage of Cr (VI) removed reached maximum values (up to 99%) in the pH range 4.0-5.3 at a resin dose of 6 g/L and Cr (VI) concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…unloaded resin has become stronger and shifted to 937 cm -1 after Cr(VI) loading. Balan et al (2013) have reported that Cr=O vibrations appear around 948.96 cm -1 and this can result an enhancement in peak intensity in the spectrum of the loaded resin. The new peak at 771 cm -1 with a significant intensity is due to the Cr-O groups (Balan et al, 2013), which again confirms the Cr(VI) loading on MIEX resin.…”
Section: Characterizationmentioning
confidence: 99%
“…unloaded resin has become stronger and shifted to 937 cm -1 after Cr(VI) loading. Balan et al (2013) have reported that Cr=O vibrations appear around 948.96 cm -1 and this can result an enhancement in peak intensity in the spectrum of the loaded resin. The new peak at 771 cm -1 with a significant intensity is due to the Cr-O groups (Balan et al, 2013), which again confirms the Cr(VI) loading on MIEX resin.…”
Section: Characterizationmentioning
confidence: 99%
“…30 If the plot q t versus t 0.5 is linear and passes through the origin, the intraparticle diffusion is the only rate-limiting step; if the plot presents multilinearity, the adsorption process is controlled by two or more steps. 28 As can be seen from Fig. 4d, there are three processes controlling the adsorption rate: (i) the rst sharper portions may be attributed to the lm diffusion; (ii) the second linear portions are the gradual adsorption stages, where the intra-particle diffusion is rate-controlling step; and (iii) the third portions are nal equilibrium stages where intraparticle diffusion starts to slow down due to low adsorbate concentration in aqueous solution as well as less number of available adsorption sites.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…Adsorption is now viewed as a superior technique for its cost-effectiveness and flexibility. Many organic and inorganic adsorbents such as activated carbon [8], graphene [9], purolite [10], chitosan [11], metal oxides [12], and biological wastes [13] have been used for wastewater treatment procedures so far. Graphene has extraordinary physical and electrical *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%